Radioisotope synovectomy in the treatment of patients with rheumatoid arthritis - R. M. Balabanova; Yu. A. Olyunin; A. M. Lila (Современная ревматология, 2019)
In a number of cases, systemic therapy for rheumatoid arthritis (RA), including disease-modifying anti-rheumatic drugs, biological agents, glucocorticoids (GCs), and nonsteroidal anti-inflammatory drugs, fails to completely suppress joint inflammatory changes in the patients. Therefore, local methods are widely used in the combination therapy of RA. Intra-articular injection of hyaluronic acid (HA) is a highly local treatment modality. HA can be used as initial therapy when it is necessary to achieve rapid clinical improvement, or at a later stage of the disease, in exacerbation of arthritis. However, in some patients the effect of intra-articular HA can be short-lasting, and a favorable result can be obtained with local radiotherapy. It is based on powerful irradiation of the inflamed synovium, which is provided by intra-articular injection of radioactive isotope colloids. In Russia, RA was successfully treated with colloidal Au-198, but its production was ceased in the 1990s, and agents for radioisotope synovectomy have been long unavailable.Tungsten-188/Rhenium-188generator has been recently designed in Russia, which allows Rhenium-188 to be obtained in clinics. Preclinical trials have shown that intra-articular injection ensures good fixation of the drug in the knee joint with its insignificant accumulation in the liver and other non-target organs and tissues. Introduction of this drug into routine clinical practice can markedly improve the efficiency of treatment in patients with chronic arthritis.